Genomes shed light on the evolution of Begonia, a mega‐diverse genus. Issue 1 (9th February 2022) - Li, Lingfei; Chen, Xiaoli; Fang, Dongming; Dong, Shanshan; Guo, Xing; Li, Na; Campos‐Dominguez, Lucia; Wang, Wenguang; Liu, Yang; Lang, Xiaoan; Peng, Yang; Tian, Daike; et al.
Summary: Clarifying the evolutionary processes underlying species diversification and adaptation is a key focus of evolutionary biology. Begonia (Begoniaceae) is one of the most species‐rich angiosperm genera with c . 2000 species, most of which are shade‐adapted. Here, we present chromosome‐scale genome assemblies for four species of Begonia ( B. loranthoide s, B. masoniana, B. darthvaderiana and B. peltatifolia ), and whole genome shotgun data for an additional 74 Begonia representatives to investigate lineage evolution and shade adaptation of the genus. The four genome assemblies range in size from 331.75 Mb ( B. peltatifolia ) to 799.83 Mb ( B. masoniana ), and harbor 22 059–23 444 protein‐coding genes. Synteny analysis revealed a lineage‐specific whole‐genome duplication (WGD) that occurred just before the diversification of Begonia . Functional enrichment of gene families retained after WGD highlights the significance of modified carbohydrate metabolism and photosynthesis possibly linked to shade adaptation in the genus, which is further supported by expansions of gene families involved in light perception and harvesting. Phylogenomic reconstructions and genomics studies indicate that genomic introgression has also played a role in the evolution of Begonia . Overall, this study provides valuable genomic resources for Begonia and suggests potential drivers underlying the diversity and adaptive evolution of this mega‐diverse clade.